Hábitos alimentarios y estado nutricional en los adultos de la parroquia San Andrés-cantón Chinchipe - Martínez Abad, Leidy Magali (2023)
Eating habits determine the selection, preparation and consumption of food. Poor eating habits lead to high rates of overweight and obesity in the adult population worldwide, which increases the risk of developing chronic non-communicable diseases such as hypertension and type 2 diabetes mellitus in the short and medium term, constituting a public health problem. The objective of this study was to determine the eating habits and nutritional status of adults between 20 and 60 years of age in the parish of San Andres-Canton Chinchipe. It was a quantitative, descriptive, cross-sectional cohort study, where a structured survey was applied with closed questions based on the Healthy Eating Index (HEI) and the taking of anthropometric measurements to determine the nutritional status according to the BMI to a sample of 142 adults between 20 and 60 years of age. In the results obtained, 52.11% (n=74) were women and 47.89% (n=68) were men. Regarding eating habits, 77.46% (n=110) had habits that need to be changed. When evaluating nutritional status, 47.89% (n=68) presented normal weight. In conclusion, the majority of the adult population of the parish of San Andrés between 20-60 years of age have eating habits that need to be changed and the nutritional status is normal